Effect of Compensation and Job Satisfaction on Employee Performance at the Residential and Land Housing Office of Cirebon Regency - Muhamad Alwi; Renaldi Rizki N (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the influence of compensation and job satisfaction on employee performance at the Cirebon Regency Office of Housing, Settlements, and Land Affairs. Employee performance is a critical factor in supporting the effectiveness of public service delivery; therefore, effective human resource management is essential through a fair compensation system and the enhancement of employee job satisfaction. This study employs a quantitative approach using an associative method to determine the relationship and influence between the variables of compensation and job satisfaction on employee performance. The study population consists of all employees at the agency, totaling 75 individuals, with a sampling technique using saturation sampling, meaning the entire population was included as respondents. Research data were obtained through the distribution of a questionnaire using a Likert scale and supported by relevant secondary data. Data analysis was conducted using multiple linear regression techniques with the aid of statistical software. This study is expected to provide an empirical overview of the role of compensation and job satisfaction in improving employee performance in local government agencies, as well as serve as a basis for organizations in formulating more effective human resource management policies.